2019
DOI: 10.20849/iref.v3i2.703
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Regional Government Characteristics of Financial Performance

Abstract: This study aims to determine the effect of regional government characteristics on the financial performance of district / city regional governments in West Kalimantan. This research uses multiple regression. The dependent variable used is the regional financial performance which is proxied from the level of efficiency while the independent variables used are total assets, regional expenditure, DAU, PAD, and leverage as indicators of local government characteristics. The findings of this study indicate that reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
1
0
3

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 3 publications
1
1
0
3
Order By: Relevance
“…Concerning marital status, the majority of the patients were married and accounted for (64.0%) The disease can usually affect individuals between the age (40-00and ˃21years) when these individuals were already married, The Study show agreement with the study of Rusmita, et al,(2008) they found that the majority of patients were married (73.0%) (13). With regard to educational level, most of the patients can read and write (28.0%).…”
Section: Discussionsupporting
confidence: 84%
“…Concerning marital status, the majority of the patients were married and accounted for (64.0%) The disease can usually affect individuals between the age (40-00and ˃21years) when these individuals were already married, The Study show agreement with the study of Rusmita, et al,(2008) they found that the majority of patients were married (73.0%) (13). With regard to educational level, most of the patients can read and write (28.0%).…”
Section: Discussionsupporting
confidence: 84%
“…The 4th amendment to the Constitution of 1945 became a significant steppingstone in redesigning the government system [16]. This refers to the principle of a fair distribution of power between the central government and regional governments, equitable distribution of the use of regional resources and wealth, and a more recognized Local Government [44].…”
Section: Discussionmentioning
confidence: 99%
“…Sari dan Mustananda (2019) [8] menggunakan total aset pemerintah daerah sebagai basis untuk mengukur ukuran pemerintah daerah. Sari Rusmita (2019) [14] juga menggunakan total aset sebagai basis untuk mengukur ukuran pemerintah daerah.…”
Section: Ukuran Pemerintah Daerahunclassified
“…Penelitian yang dilakukan oleh Sari Rusmita (2019) [14] menemukan bahwa terdapat hubungan positif yang tidak signifikan antara ukuran pemerintah daerah dengan kinerja keuangan daerah. Di lain sisi Ni Made Diah Permata Sari dan I Ketut Mustanda (2019) [8] menemukan bahwa terdapat hubungan negatif yang signifikan antara ukuran pemerintah daerah dengan kinerja keuangan daerah.…”
Section: H3: Belanja Modal Berpengaruh Positif Terhadap Kinerja Keuangan Pemerintah Kota Dan Kabupaten DI Provinsi Sumatera Utara Hubungaunclassified
See 1 more Smart Citation